High-throughput screening of antibody variants for chemical stability: identification of deamidation-resistant mutants. Issue 7 (3rd October 2018) - DiCara, Danielle M.; Andersen, Nisana; Chan, Ruby; Ernst, James A.; Ayalon, Gai; Lazar, Greg A.; Agard, Nicholas J.; Hilderbrand, Amy; Hötzel, Isidro
ABSTRACT: Developability assessment of therapeutic antibody candidates assists drug discovery by enabling early identification of undesirable instabilities. Rapid chemical stability screening of antibody variants can accelerate the identification of potential solutions. We describe here the development of a high-throughput assay to characterize asparagine deamidation. We applied the assay to identify a mutation that unexpectedly stabilizes a critical asparagine. Ninety antibody variants were incubated under thermal stress in order to induce deamidation and screened for both affinity and total binding capacity. Surprisingly, a mutation five residues downstream from the unstable asparagine greatly reduced deamidation. Detailed assessment by LC-MS analysis confirmed the predicted improvement. This work describes both a high-throughput method for antibody stability screening during the early stages of antibody discovery and highlights the value of broad searches of antibody sequence space.